Folic acid restricts SARS-CoV-2 invasion by methylating ACE2 - Zhang, Yuanzhou; Pang, Yechun; Xu, Baiyin; Chen, Xingshi; Liang, Shunshun; Hu, Jingying; Luo, Xiaoying (Frontiers in Microbiology, 2022)
The current COVID-19 pandemic is motivating us to elucidate the molecular mechanism of SARS-CoV-2 invasion and find methods for decreasing its transmissibility. We found that SARS-CoV-2 could increase the protein level of ACE2 in mice. Folic acid and 5-10-methylenetetrahydrofolate reductase (MTHFR) could promote the methylation of the ACE2 promoter and inhibit ACE2 expression. Folic acid treatment decreased the binding ability of Spike protein, pseudovirus and inactivated authentic SARS-CoV-2 to host cells. Thus, folic acid treatment could decrease SARS-CoV-2 invasion and SARS-CoV-2-neutralizing antibody production in mice. These data suggest that increased intake of folic acid may inhibit ACE2 expression and reduce the transmissibility of SARS-CoV-2. Folic acid could play an important role in SARS-CoV-2 infection prevention and control.